Development of Cultural Ecotourism-Based Microlearning Videos for Trading-Company Accounting - Pransida Budaya; Dessy Wardiah; Neta Dian Lestari (Yayasan Sembilan Pemuda Indonesia, 2027)
This study developed a microlearning teaching video for trading-company accounting by integrating visual content from South Sumatran cultural ecotourism, designed to address low student learning absorption, monotonous text-based instruction, and the difficulty of understanding abstract accounting concepts at SMKN 1 OKU Selatan. Educational Research and Development using the ADDIE stages (Analysis, Design, Development, Implementation, Evaluation) was employed. Data were collected through classroom observation, teacher interviews, expert validation sheets, student response questionnaires, implementation observation, and pre-test and post-test measures. The final three-minute Full HD video presented trading company concepts through contextual illustrations of packaged coffee, coffee plantations, Danau Ranau, and local cultural elements. Expert validation yielded a 90% feasibility score (highly feasible). Implementation showed student enthusiasm at 92%, ease of access at 88%, and content interaction at 85%. Learning scores increased from 54.20 (pre-test) to 86.50 (post-test), with a normalized gain of 0.70 (strong improvement), and mastery criterion achievement rose from 55% to 92%. This study uniquely integrates local cultural ecotourism visuals into microlearning accounting videos, an underexplored combination in vocational education. Short, locally contextualized videos reduce perceived complexity, sustain attention, and connect vocational concepts with students' immediate environment. This research contributes a feasible, practical, and effective instructional product for trading-company accounting, offering a replicable model for vocational schools seeking culturally responsive and technology-enhanced learning solutions.